1997
DOI: 10.1111/j.1445-2197.1997.tb01905.x
|View full text |Cite
|
Sign up to set email alerts
|

Breast Metastases From Primary Leiomyosarcoma

Abstract: Two cases of metastatic leiomyosarcoma of the breast are presented. The reasons why they are considered as secondary tumours and not primary tumours are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
1
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 3 publications
0
7
1
1
Order By: Relevance
“…Our primary sources of breast metastasis were: non-Hodgkin's lymphoma; uterine leiomyosarcoma; Merckel cell carcinoma; and intestinal stromal sarcoma. Two previous studies had reported breast metastasis arising from primary leiomyosarcoma similar to our case 2 [11,13], but the uterine origin has not been previously reported, although histological confirmation of primary tumour in our case 2 is not available. One case report [12] described a Merckel cell carcinoma metastatic to the breast similar to our case 3.…”
Section: Discussioncontrasting
confidence: 58%
“…Our primary sources of breast metastasis were: non-Hodgkin's lymphoma; uterine leiomyosarcoma; Merckel cell carcinoma; and intestinal stromal sarcoma. Two previous studies had reported breast metastasis arising from primary leiomyosarcoma similar to our case 2 [11,13], but the uterine origin has not been previously reported, although histological confirmation of primary tumour in our case 2 is not available. One case report [12] described a Merckel cell carcinoma metastatic to the breast similar to our case 3.…”
Section: Discussioncontrasting
confidence: 58%
“…La bilatéralité est rapportée dans 28 % des cas. Les sarcomes, et plus particulièrement les leiomyosarcomes, donnent rarement des métastases mammaires, à notre connaissance seulement neuf cas ont été publiés dont quatre cas étaient d'origine utérine [1,3,4,14,16,18,19]. Le choriocarcinome est également rarement à l'origine de métastase mammaire, en effet seulement dix cas ont été déjà rapportés [3,12,13,[20][21][22], dans un seul cas la méta-stase était révélatrice du choriocarcinome [21].…”
Section: Discussionunclassified
“…There are only eight reported cases of leiomyosarcomas metastatic to the breast with our case representing the ninth. [10][11][12][13][14][15][16] Primary tumors in the other cases were located in the kidney, endocervix, soft tissues, endometrium and mesocolon. To the best of our knowledge this is the first case of retroperitoneal leiomyosarcoma metastasizing to the breast.…”
Section: Discussionmentioning
confidence: 99%